Al-Qaradawi’s juristic perspectives on zakah of agricultural wealth as reflected in his Fiqh Al Zakah / Muhammad Ikhlas Rosele, Luqman Abdullah and Mohd Anuar Ramli - Rosele, Muhammad Ikhlas; Abdullah, Luqman; Ramli, Mohd Anuar (Universiti Teknologi Mara Selangor, 2013)
This paper discusses al Qaradawi’s perspective on several issues in zakah of agricultural wealth. It analyzes his juristic views on the issues as reflected in his master piece Fiqh al Zakah. This paper focuses mainly on three issues, namely, nisab of agriculture, deduction of debts and expenses and zakah on rented land. It is found out that al Qaradawi’s perspectives on zakah of agricultural wealth based on the maqasid and he goes beyond the typical approaches of many Muslim scholars who only rely on the usul fiqh methods in deducing the rulings from the legal texts in Al Quran or Al Sunnah.